Exil und Identität : Die italienischen Juden in der Schweiz (1943-1945). - Longhi, Silvano (Bibliothek des Deutschen Historischen Instituts in Rom., 2017)
The series Bibliothek des Deutschen Historischen Instituts in Rom (Library of the German Historical Institute in Rome) was established in 1905. It produces academic monographs and volumes of collected essays on Italian and German history from the Early Middle Ages until the recent past.